The Role of Sabhara Patrol to Reduce the Crime of Theft in the Jurisdiction of the Bogor City Police - Gemilang, Surya Dwi Aji (Police Studies Review, 2024)
West Java is still ranked first in terms of the number of cases of Motorized Vehicle Theft (CURANMOR). Polresta Bogor as one of the police institutions that has the responsibility to maintain the security and involvement of the people of Bogor City carries out three efforts consisting of preventive, repressive, and preemptive efforts. Patrol is one of four preventive prevention efforts. According to the Regulation of the Head Republic Indonesia National Police Security Preservation Agency Number 1 of 2017 concerning Patrol, patrol is a form of mobile activity from one place to a certain place carried out by members of Sabhara Indonesian National Police in order to prevent an act of crime, providing a sense of security, protection and protection to Public. This study aims to determine the role, management, and obstacles of patrol activities carried out by the Sabhara Unit to Reduce Criminal Acts in the City of Bogor City Police Jurisdiction. This study uses a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results showed that the management of patrol activities carried out by the Sabhara Unit in preventing criminal acts of fraud in the Bogor City Police jurisdiction into four stages are planning, organizing, actuating and controlling. The role of patrol activities carried out by Sabhara Unit to reduce criminal acts of fraud in the jurisdiction of the Bogor City Police is to carry out carrying out preventive and repressive efforts. The obstacle in the implementation of patrol activities carried out by the Sabhara Unit to reduce criminal acts of fraud in the jurisdiction of the Bogor City Police is the lack of a fuel oil (BBM) budget.